2022
DOI: 10.3390/fluids7070212
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction by Wingtip-Mounted Propellers in Distributed Propulsion Configurations

Abstract: Tip-mounted propellers can increase wing aerodynamic efficiency, and the concept is gaining appeal in the context of hybrid electrical propulsion for greener aviation, as smaller and lighter electrical motors can help with mitigating structural drawbacks of a tip engine installation. A numerical study of tip propeller effects on wing aerodynamics is herein illustrated, considering different power configurations of a Regional Aircraft wing. A drag breakdown analysis using far-field methods is presented for one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Irrespective of the direction of rotation and thrust, stall is observed at AoA = 16° for tip-tractor configuration. Sinnige et al (2019, 2021) and Minervino et al (2022) observed a similar trend in their studies with the propeller at the tip in tractor configuration.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Irrespective of the direction of rotation and thrust, stall is observed at AoA = 16° for tip-tractor configuration. Sinnige et al (2019, 2021) and Minervino et al (2022) observed a similar trend in their studies with the propeller at the tip in tractor configuration.…”
Section: Resultssupporting
confidence: 63%
“…Having a swirling flow at the tip which has an opposite rotation to the wing tip vortex increases aerodynamic efficiency. Snyder and Zumwalt (1969) (experimental), Miranda and Brennan (1986) (analytical), Sinnige et al (2019) (experimental) and Minervino et al (2022) (computational) used propellers at wing tips in tractor configuration which resulted in reduced induced drag and increased wing aerodynamic efficiency. Sinnige et al (2019) compared the tip-mounted tractor configuration with conventional one and found that inboard-up rotating propeller at wing tip results in better aerodynamic efficiency than the conventional configuration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the takeoff, the propellers will spin, and, by creating a swirl, the high-frequency rotation will act against the wingtip vortex, decreasing both its intensity and the strength of downwash. Moreover, the propeller's advantage (decrease in induced drag) outweighs its potential disadvantage (increase in skin friction drag due to the wing behind the propeller's slipstream) [12].…”
Section: Introductionmentioning
confidence: 99%
“…(2019) demonstrated from experimental studies that the reduction in drag promoted by a wingtip-mounted propeller is due to a reduction in the downwash experienced by the wing because of a combination of wingtip-vortex attenuation and swirl recovery that occur with a wingtip-mounted propeller rotating inboard-up. In these conditions, an increase in effective aspect ratio and consequent reduction of induced drag is obtained (COLE et al, 2021;MINERVINO et al, 2022;SINNIGE et al, 2019;SNYDER;ZUMWALT, 1969). In addition, the local increase in dynamic pressure in the portion of the wing washed by the propeller slipstream increases the lift generated (AREF et al, 2018;SINNIGE et al, 2019).…”
Section: Aerodynamics and Aeroacoustics Of Propellers Installed On De...mentioning
confidence: 99%